ESTABLISHING, STRUCTURE AND SELECTION OF JUDGES IN THE EUROPEAN COURT OF HUMAN RIGHTS - Petrov, Nenad (Journal of process management and new technologies, 2019)
Main purpose of this paper is to review the development and organizational structure of the European Court of Human Rights in Strasbourg, primarily the idea of​establishing such body is to ensure the protection of the rights guaranteed in the Convention of Human Rights and the same are being violated by countries petitioners, the problems which have arisen in its functioning, the reforms which have been carried out in order to resolve such problems, until its present form. In addition, we will pay attention to its organizational structure –selection and structure of the court.